Analisis Tingkat Penguasaan Kata Baku Bahasa Indonesia Oleh Mahasiswa Administrasi Perkantoran Stambuk 2024 Universitas Negeri Medan: Penelitian - Guruh Real Agave Nababan; Sry Rejeki Lumbantoruan; Nurlita Safrani; Andika Rifky Maulan; Ibnu Sina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Indonesian plays a crucial role, both as a national identity and as the official language of the country. One fundamental aspect of its proper use lies in mastering and applying standard vocabulary. In practice, many students are still inconsistent in using standard words, both in writing and in academic communication, thus affecting the quality of their scientific language. This study aims to analyze the level of mastery of standard Indonesian vocabulary among Office Administration students, class of 2024, at Medan State University. This study used a quantitative descriptive approach with a questionnaire consisting of 20 multiple-choice questions distributed via Google Forms. The study sample consisted of 30 randomly selected students. Data were analyzed through item validity tests, instrument reliability using Cronbach's Alpha, and analysis of percentage word mastery. The study findings indicate that students' mastery of standard vocabulary is at a moderate level with an average score of 67,7%. These results indicate a gap between the expected mastery of standard vocabulary and students' actual competencies. Therefore, more innovative and contextual language learning strategies are needed to help students improve their academic and practical language skills.